Analisis Model dan Pendekatan Dakwah Kiai Muda di Era Digital - Khairuddin Khairuddin; Bayu Pradana (Fakultas Dakwah Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2025)
Da'wah activities in the digital era are a necessity in preaching. Where da'wah activities usually utilize various digital platforms and social media such as YouTube, Instagram, TikTok, Facebook and so on. This article focuses on how young clerics such as Gus Iqdam, Gus Miftah and Gus Kautsar preach through YouTube social media. Theoretically there is a gap between the principle of a preacher who must speak well, but the three young kiai instead use it as a method in preaching. The research method in the article uses qualitative with communication theory as an analytical tool. So the use of